Clustering Productivity of Rice in Karawang Regency Using the Fuzzy C-Means Method - Suna Mulyani; Betha Nurina Sari; Azhari Ali Ridha (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Rice is a major food commodity that has a strategic role in the development of community nutrition, agriculture and the economy in Indonesia. Karawang Regency is known as a city of rice barns which is one of the largest rice producing and supplying regions in the province of West Java and even Indonesia. The importance of rice as a staple food in Karawang Regency needs to ensure rice productivity remains stable. Data Mining is a data mining technique that produces an output in the form of knowledge. The purpose of this study is to classify the productivity of rice plants so as to know the area of high rice productivity in Karawang Regency. The data used in this study were 180 data from 30 districts. Data grouping will use the Fuzzy C-Means (FCM) algorithm which is a data clustering technique where the existence of each data point in a cluster is determined by the degree of membership. With Silhouette Coefficient evaluation techniques the results of clustering obtained in 2010, 2011, 2013, 2014 and 2015 show that the results of grouping have a good structure that is above 0.5. Only in 2012 showed that the grouping results had a weak structure of 0.49.